Digital & media literacy as a condition for the formation of the digital generation - Andriievska, V.; Shinkaryova, D. (New Collegium, 2022)
The article shows that the formation of the digital generation today takes place in difficult crisis conditions. It causes the need to rethink and apply new methodological tools, didactic approaches that will meet the requirements of modernity and the needs of the individual. It was analyzed by the "theory of generations" and it was determined that the vast majority of students today are the digital generation. It is substantiated that for the digital generation, standard teaching methods lose their effectiveness. In this context, it is shown that the orientation of the goals and content of school education to the development of "4K digital skills" in students: critical thinking, creativity, communication skills, cooperation becomes especially relevant. It was clarified that working with information occupies a prominent place in the problem of developing "4K digital skills" among students. "4K digital skills" are characterized. It was concluded that the development of the considered digital skills among schoolchildren is successfully implemented within the course "Digital and media literacy".